The Lady of the Angels and Her City - Wright, Wendy M. (Book collections on Project MUSE., 2013)
The Lady of the Angels and Her City recounts Wendy Wright's visitations to her hometown's many Marian churches and shrines. But it is much more than a personal pilgrimage narrative. It offers important glimpses into the history of Los Angeles Catholicism, American Catholic culture, and Mary's place in Catholic theology and tradition. It peeks into the heroic labors of the religious orders that went on mission there and the waves of immigrants who have arrived on American shores. With Wright, readers will consider: * the relationship between the vivid devotional faith of a people and their common worship. * the cosmic vision of the Hispanic and Filipino faithful and its differences from that held by most post-Vatican II Americanized Catholics. * the possibility of relating to a Mary who is the apocalyptic Virgin of Fatima and yet also 'always our sister'. * the unheard and undervalued voices of those who, across the theological and cultural spectrum, find in Mary a companion, an advocate, and a deeply consoling presence. Readers who know the geography of Los Angeles Catholicism will surely enjoy Wright's reflection on familiar places. But there is much here that will fascinate anyone interested in either the history of Christianity in America or devotion to Mary by those who love her today.